Teachers Perspectives on One-on-One Remote Piano Lessons in Selected High Schools in Cape Town - Kim, Gyu Min (College of Music, 2025)
The study examines how piano teachers employed at Quintile 5 public high schools in Cape Town adjusted to conducting online piano lessons during the COVID-19 restrictions on face-to-face teaching. Following the announcement of a national lockdown, schools in South Africa had to transition rapidly to online methods of teaching in April 2020, and as a result, many piano teachers had to transform their conventional methods of teaching into online instruction. Very few studies exist on online methods of teaching, especially in the practical instruction of a musical instrument, and even fewer in the South African context. The study aims to address this gap in the literature by focusing on the impact of online teaching during the COVID-19 pandemic on teachers, learners, and school environments in Cape Town. At the centre of the study are the personal experiences of piano teachers who taught online during the COVID-19 pandemic, and thus a qualitative approach was followed. Data was collected via short questionnaires and semi-structured interviews with seven piano teachers from seven different Quintile 5 schools in Cape Town. The data was then analysed with qualitative coding. As theoretical framework, Jack Mezirow's Transformative Learning Theory was selected as it posits that, following a disorienting dilemma, individuals can undergo profound changes in their perspectives through critical reflection. This study reveals diverse perspectives on the shift to online teaching among participants, many of whom initially struggled with the transition. Despite facing obstacles, participants proactively improved their online piano lessons through careful planning, involving the parents, setting specific goals, and offering emotional support. Schools also played a pivotal role, offering different support systems, ranging from providing counselling to learning materials. Teachers extended personal help to their learners by maintaining regular communication, an empathetic approach in lessons, and tailored guidance for learners who did not own a proper instrument. Participants still continue to use some of the said methods in face-to-face teaching, which suggests that they transformed their teaching methods on a long-term basis. This research touches on the socio-economic aspect of education, but it fell outside the scope of the study to investigate this in detail. Further research is thus required to fully comprehend the relationship between South African learners' socio-economic status and their academic progress during the COVID-19 pandemic.